Factors associated with surgical outcomes of cervical ossification of the posterior longitudinal ligament. Issue 29 (July 2018) - Yudoyono, Farid; Cho, Pyung Goo; Park, Sang Hyuk; Moon, Bong Ju; Yi, Seong; Ha, Yoon; Kim, Keung Nyun; Yoon, Do Heum; Shin, Dong Ah
Abstract : Abstract: To investigate factors associated with surgical outcomes of cervical ossification of the posterior longitudinal ligament (OPLL). This retrospective study included patients (662 males and 251 females; mean age 55.8 years) with symptomatic OPLL. All patients had been diagnosed with OPLL based on cervical magnetic resonance imaging and computed tomography scans. Demographic, surgical outcome was measured using visual analog scale (VAS) and Japanese Orthopedic Association (JOA) scale scores. The results of our study indicated radicular pain was more common in segmental and circumscribe OPLL subtypes ( P < 0.05). An anterior approach was favored in patients with less than 3 involved vertebral levels ( P < 0.05). All surgical methods showed good outcomes ( P < 0.05). Continuous and mixed OPLL subtypes showed worse surgical outcome with higher VAS and JOA scores ( P < 0.05). Laminoplasty and anterior cervical discectomy and fusion were significantly associated with a higher recovery rate ( P < 0.05). Among these patients, there were more complications with the anterior approach ( P < 0.05). Male gender, open door laminoplasty ipsilateral, and ipsilateral-to-symptom-side opening were associated with postoperative C5 palsy ( P < 0.05). Cervical OPLL may cause myelopathy, surgery is a safe and effective treatment for OPLL. There were no differences in clinical outcome according to surgical type, but complication rates varied depending on sex and surgical approach to symptom.